Analisis Tingkat Kematangan Pelayanan Pada PT Telkom Sampit dengan Menggunakan Domain COBIT 5 DSS02 dan DSS03 - Yusril Yusuf; Edo Tio Gunawan; Rakhma Sarita (Journal of Information System Research (JOSH), 2021)
PT Telkom Sampit is one part of PT Telekomunikasi Indonesia (Persero) Tbk (Telkom) which contributes in meeting the communication and information needs of the community. PT Telkom Sampit provides several product services, namely Wifi.id, IndiHome and UseeTV. Thus, Telkom Sampit must provide good services in managing services. As for some of the obstacles that often occur including problems, slow and damaged. From these problems, it is necessary to measure the level of service improvement at PT Telkom Sampit using the COBIT 5 framework focusing on the domains DSS02 (Managing Service Requests) and DSS03 (Managing Problems). Based on research that has been done PT Telkom Sampit is at level 4, namely Predictable Process, which is included in a good level for a company, although it is not in accordance with estimates that should be at level 5, namely Optimizing Process (Optimization Process). With this research, it is hoped that it can be used as an evaluation in improving the quality of service performance at PT. Telkom Sampit in serving customers.